Batrachochytrium salamandrivorans is necronotic: carcasses could play a role in Bsal transmission - Carter, E. Davis; DeMarchi, Joseph A.; Wilber, Mark Q.; Miller, Debra L.; Gray, Matthew J. (Frontiers in Amphibian and Reptile Science, 2024)
Introduction Batrachochytrium salamandrivorans (Bsal) poses a major threat to global amphibian biodiversity. It is essential we understand Bsal transmission to develop better-informed management strategies. Infected carcasses are an important source of transmission for several human and wildlife disease systems; however, they have not been examined as sources for Bsal exposure. Here, we evaluated whether infected newt carcasses could contribute to Bsal transmission dynamics. Methods We cohoused infected carcasses with susceptible newts in two cohousing chamber types (partitioned or non-partitioned) at three timepoints post-mortem ([0,24[, [24,48, [48,72] hrs). The partitioned chamber prevented newt-to-newt contact hence only allowed indirect, waterborne transmission of zoospores. We measured shedding rates of infected carcasses at each post-mortem timepoint and monitored infection status and mortality of susceptible newts which were exposed during cohousing events. Results Our results indicate carcasses are capable of transmitting Bsal to susceptible newts up to at least 72 hrs post-mortem, even without live newts directly contacting carcasses. All susceptible newts in each chamber type and post-mortem period became infected and >90% experienced disease-induced mortality. Bsal genomic copies/uL in skin swabs taken from infected carcasses were high, averaging 7.4x105, 8.6x105, and 2.0x106 at 24, 48, and 72 hrs post-mortem, respectively. Water samples collected from cohousing chambers averaged 2743 Bsal genomic copies/uL (approximately 1357 zoospores) and did not decline over 72 hrs. Discussion Our results indicate Bsal infection can occur rapidly between infected carcasses and susceptible aquatic salamanders via indirect and direct transmission pathways, and carcasses may prolong outbreaks by increasing the duration that infected individuals remain infectious. Carcass removal may be a strategy to reduce Bsal transmission and the impacts of outbreaks.